CARDIOVASCULAR RISK ASSOCIATED WITH ANDROGEN DEPRIVATION THERAPY IN ADVANCED PROSTATE CANCER - DENNY, DEEPTHI C; SS, YOGAVADULA; R, VIJAY; FARDAN, MOHAMED; IYPE, DIVYA SARA; K, ABI MAHESHWARAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Cancer is a lethal disease that is the second leading cause of mortality in the world. According to statistics, prostate cancer is one of the most common types among men. Male hormone androgens, particularly testosterone, are required for normal growth and functioning of the prostate. In prostate cancer, activation of the androgen receptor promotes the growth of cancer cells. The goal of hormonal therapy or androgen deprivation therapy (ADT) is to reduce levels of such male hormones in the body or prevent them from stimulating cancer cells. There are many issues that have to be considered before initiation of hormonal therapy which are necessary to be aware of for its prevention and the management in routine clinical practices. In this review article, we emphasis on cardiovascular complications following ADT and certain treatment measures.